4(-6x – 3) + 24x = -72x + 132
Step 1 -24x – 12 + 24x = -72x + 132 Distribute Property of Equality
Step 2: –12 = -72x + 132 equivalent
Step 3: -144 = -72x Subtraction Property of equality
Step 4: 2 = x Equivalent / Division property of equality
Answer:
-184
Step-by-step explanation:
First we plug in -14 into the x's.
4 (-14) - 8(2 - (- 14))
Then we can distribute the 8.
4 (-14) - 16 - 112
Then solve from here.
-56 - 16 - 112
= -184
Answer:
The correct answer would be chart A.
Step-by-step explanation:
Answer:
First option
Step-by-step explanation:
You can plug in values and verify.
Please help me by marking me brainliest. I'm really close :)